Differential diagnosis of fibrous dysplasia - László Simonffy; Szabolcs Gyulai-Gaál; Csaba Dobó Nagy; Bence Tamás Szabó (Hungarian Dental Association, 2018)
Following taking the medical and dental history and performing a stomato-oncological screening of a 69-year-old female patient referred to our department, a panoramic X-ray acquisition was taken. On the panoramic image multiple sclerotic and cyst-like lesions were visible in the mandible. Based on the radiological findings, the use of further imaging modalities was needed. Posteroanterior (PA) and lateral (LAT) skull and cone beam CT (CBCT) images were taken. Except for the mandibular bone no abnormalities were found in other areas of the skull on the PA and LAT skull radiographs. No chest X-ray acquisition has been taken from the patient within the last five years. On the basis of available medical history, patient's examination data and radiographic images monostotic fibrous dysplasia has been predicted as radiologic diagnosis. Fibrous dysplasia is a benign developmental failure of the bone, which can involve one (monostotic type) or more bones (polyostotic type). During the bone remodeling the osseus structures are replaced by immature fibro-osseous tissue. A precise diagnosis of fibrous dysplasia usually cannot be made without using appropriate radiologic imaging modalities.